The Future of Education in Ghana: Critical Education for Socio-Economic Development - Nkansah, Joan Nkansaa (Journal of Interdisciplinary Studies in Education, 2021)
This research explores how critical education can contribute to the development of critical human capital relevant to Ghana’s socio-economic development. Many classroom teaching and learning in Ghana follow a rigid curriculum with limited or no classroom interaction, which restrict students’ creativity and critical consciousness. A systematic literature review was conducted using scholarly articles and books. The research identified four concepts that (i.e., problem-posing education, teacher and student roles, praxis, and dialogue) promote critical education. The research revealed the following about education: education should be about the critical examination of the social world, resulting in actions that serve the best interest of society. The research concluded that critical education could empower students to become critical thinkers, problem-solvers, and change agents who can champion the cause for Ghana’s socio-economic development.